ANALISIS KESELAMATAN DAN KESEHATAN KERJA DENGAN PENDEKATAN ERGONOMI STUDI KASUS CAHYA SETYA TROPHY - Muchamad Afif Abdulloh; Nur Muflihah; Minto; Sulung Rahmawan Wira Ghani (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2023)
Cahya setya trophy is a small manufacturing industry that produces trophies, vandels, acrylics, etc. In this small industry in the warehouse, there is still a lack of awareness to use personal protective equipment and a work method that can cause Musculosketal disorders. This study aims to analyze K3 from the Cahya setya trophy warehouse using observation methods, Nordic Body Map, RULA and REBA. The observation method was used for the initial step of the study and the Nordic Body Map was used to find a sample as a research from the RULA, REBA method. The results of work safety observations found that the dangerous action if not wearing shoes was the worst possibility that it could cause the employee's feet to bruise, and not using gloves was the worst possibility that the hands could be scratched. The results of the occupational health analysis using the REBA method, the bent position got a final score of 8, the duct tape process squat position got 9 scores, both positions had an action level of 3, and the packaging squat position got a score of 12 with an action level of 4, which means there is a very high risk and this position is very dangerous, then change action is needed, The results of the RULA method in the packaging squat position, the duct tape squat got a score of 6 which had an action level of 3 and the bent position got a score of 7 which had an action level of 4. From the results of these calculations, all work methods require action to change work methods, if changes in work methods are not immediately carried out, it can trigger Musculosketal disorders and lack of comforted at work.